Comparative analysis of the secretomes of Schizophyllum commune and other wood-decay basidiomycetes during solid-state fermentation reveals its unique lignocellulose-degrading enzyme system. Issue 1 (December 2016) - Zhu, Ning; Liu, Jiawen; Yang, Jinshui; Lin, Yujian; Yang, Yi; Ji, Lei; Li, Meng; Yuan, Hongli
Abstract Background The genome ofSchizophyllum commune encodes a diverse repertoire of degradative enzymes for plant cell wall breakdown. Recent comparative genomics study suggests that this wood decayer likely has a mode of biodegradation distinct from the well-established white-rot/brown-rot models. However, much about the extracellular enzyme system secreted byS. commune during lignocellulose deconstruction remains unknown and the underlying mechanism is poorly understood. In this study, extracellular proteins ofS. commune colonizing Jerusalem artichoke stalk were analyzed and compared with those of two white-rot fungiPhanerochaete chrysosporium andCeriporiopsis subvermispora and a brown-rot fungusGloeophyllum trabeum . Results Under solid-state fermentation (SSF) conditions, S. commune displayed considerably higher levels of hydrolytic enzyme activities in comparison with those ofP. chrysosporium, C. subvermispora andG. trabeum . During biodegradation process, this fungus modified the lignin polymer in a way which was consistent with a hydroxyl radical attack, similar to that ofG. trabeum . The crude enzyme cocktail derived fromS. commune demonstrated superior performance over a commercial enzyme preparation fromTrichoderma longibrachiatum in the hydrolysis of pretreated lignocellulosic biomass at low enzyme loadings. Secretomic analysis revealed that compared with three other fungi, this species produced a higher diversity of carbohydrate-degrading enzymes, especially hemicellulases and pectinases acting on polysaccharide backbones and side chains, and a larger set of enzymes potentially supporting the generation of hydroxyl radicals. In addition, multiple non-hydrolytic proteins implicated in enhancing polysaccharide accessibility were identified in theS. commune secretome, including lytic polysaccharide monooxygenases (LPMOs) and expansin-like proteins. Conclusions Plant lignocellulose degradation byS. commune involves a hydroxyl radical-mediated mechanism for lignocellulose modification in parallel with the synergistic system of various polysaccharide-degrading enzymes. Furthermore, the complex enzyme system ofS. commune holds significant potential for application in biomass saccharification. These discoveries will help unveil the diversity of natural lignocellulose-degrading mechanisms, and advance the design of more efficient enzyme mixtures for the deconstruction of lignocellulosic feedstocks.